Tourism: Asian country ranking using analytic hierarchy process - Crisostomo, Anna Sheila I. (Animo Repository, 2019)
Ten Asian countries are analyzed and ranked according to four major tourism factors namely: food, tourism spots in the country, security and cost of living. This is done to determine the best tourist destination in a certain point in time. Analytic Hierarchy Process (AHP) is the methodology utilized in in computing the ranks of the ten countries. These ranks can be used for tourism promotions, recognitions and even in deciding where to travel for holidays and leisure purposes. The weights of the four factors (food, tourist destinations, security and cost of living) can be adjusted in accordance to the priority of the person for choosing which country to visit or an agency that will recognize tourism ranks among Asian countries. The presented process yields a maximum consistency ratio of 8.55%. © 2019 IEEE.